Penerapan Teknologi Penggunaan Tumbuhan Alami Untuk Menghilangkan Daya Rekat Telur Ikan Baung pada Kelompok Perikanan Sawah Mandiri, Desa Sawah, Kecamatan Kampar Utara, Kabupaten Kampar - Sukendi, Sukendi; Putra, Ridwan Manda; Zulkarnaini, Zulkarnaini; Heltina, Desi; Nurhidayah, Tengku (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The purpose of the community service activities carried out is to provide knowledge about the application of technology using natural plants to eliminate the adhesion of Asian Redtail Catfish eggs to the Sawah Mandiri Fisheries Group, Sawah Village, North Kampar District, Kampar Regency. The methods used in this community service activity is the lecture, discussion and practice/demonstration in the field. The lecture method was carried out in the meeting room of the head of the Sawah Mandiri Fisheries Group, Sawah Village, North Kampar District, Kampar Regency by providing material on the technology of using natural plants. The practical method was carried out by direct demonstration in the field about all the material that had been given previously. The results of the evaluation of changes in knowledge carried out on 15 participants in the activity shown that 11 people (73.33%) were able to absorb the material provided with a very good predicate, 3 people (20%) were able to absorb the material provided with a good predicate, 1 person (6.67%) was able to absorb the material with a sufficient predicate while those who obtained a very poor predicate and a poor predicate were not found. The results of the skills evaluation show that members of the Sawah Mandiri Fisheries Group have been able to practice directly the activities that have been given in the field about the technology. While the results of the impact evaluation show that members of the Sawah Mandiri Fisheries Group enthusiastic started to used this technology in fish hatcheries.